El estudio de los fondos de la Biblioteca Francisco Zabálburu - Llera Llorente, M.ª Teresa (Revista General de Información y Documentación, 2006)
The current article pretends to present one of Spain’s most important library collections, unknown by a lot of book lovers. After a short story about its formation, we describe the contents of the cupboards, from the oldest manuscript (IX century) to the most recent piece. The study takes into account different aspects such as the rarity, the study of matters, bindings, printers, etc.
Keywords: Bibliophilism; Old book; Collecting; Manuscript